2016
DOI: 10.1089/cyber.2016.0182
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Smoking and Problematic Internet Use Among Japanese Adolescents: Large-Scale Nationwide Epidemiological Study

Abstract: The aim of this study was to clarify the association between smoking and problematic Internet use (PIU), such as Internet addiction (IA) and excessive Internet use (EIU), among Japanese adolescents. A self-administered questionnaire was administered to students enrolled in randomly selected junior and senior high schools throughout Japan. Responses were obtained from 100,050 students (0.94:1 ratio of boys to girls). The prevalence of IA (as indicated by a Young Diagnostic Questionnaire for Internet Addiction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
3
24
4
Order By: Relevance
“…This result was similar to the result of Mihara et al . and Morioka et al . for junior high and high school students in Japan.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result was similar to the result of Mihara et al . and Morioka et al . for junior high and high school students in Japan.…”
Section: Discussionsupporting
confidence: 92%
“…According to a review of Internet addiction among youth in Japan, there were 11 publications as of 2014 in which no Englishlanguage papers were reported. 33 Following this review, some new studies by Tateno et al, 19 Hirao, 34 Morioka et al, 14,34 and So et al 28 were reported.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings show that PIU is a potential significant risk factor of smoking. Results corroborate with those previous studies showing a significant association between IA and smoking [26,27] and extend the knowledge that smoking is also associated with SNA. Addiction with the Internet may interfere with normal, adaptive functioning, leading to engagement in risky behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a few studies have documented the association between PIU and smoking. For example, one study investigated the association of smoking and PIU among adolescents reported a dose-dependent relationship between smoking and IA, in which IA tended to increase with current smoking habit or the number of cigarette smoked [26]; a longitudinal study among high school students in China and USA reported a positive predictive relationship between baseline compulsive Internet use and change in substance use (which included smoking) at one-year follow-up among female students [27].…”
Section: Introductionmentioning
confidence: 99%